1988
DOI: 10.1016/0014-5793(88)80111-x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine and testosterone transcriptionally regulate renin gene expression in the submaxillary gland of normal and transgenic mice carrying extra copies of the Ren2 gene

Abstract: Expression of the mouse renin genes (Renl and Ren2) in the submaxillary gland of female mice has been analyzed following administration of thyroxine (T4) or dihydrotestosterone (DHT). Both hormones appear to act independently on mRNA accumulation which increases about 5 fold over basal level. In vitro transcription assays in isolated nuclei demonstrate that both hormones act at the transcriptional level. The effects of DHT and T4 were also analyzed in transgenic mice obtained by microinjection of the Ren2 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Plasma renin concentration was 100-fold higher in mice with two renin genes than in those with one renin gene. In addition, Ren-2 has been found to be an androgen-responsive gene and is expected to be more activated in males than in females (13,38). In line with this notion, genetic deletion of the Ren-1 gene in 129/Sv mice produces hypotension in females but not in males (7), indicating involvement of Ren-2 in a sexually dimorphic mechanism in the control of blood pressure.…”
Section: Discussionmentioning
confidence: 89%
“…Plasma renin concentration was 100-fold higher in mice with two renin genes than in those with one renin gene. In addition, Ren-2 has been found to be an androgen-responsive gene and is expected to be more activated in males than in females (13,38). In line with this notion, genetic deletion of the Ren-1 gene in 129/Sv mice produces hypotension in females but not in males (7), indicating involvement of Ren-2 in a sexually dimorphic mechanism in the control of blood pressure.…”
Section: Discussionmentioning
confidence: 89%
“…Several in vitro studies have shed further light on exactly how thyroid hormone may be influencing renin gene expression. For instance, in transgenic mice carrying extra copies of the Ren2 gene, thyroid hormone has been demonstrated to increase renin mRNA accumulation by directly stimulating transcription and/or stabilizing precursor renin mRNA (29,59). Additional studies using Calu-6 cells have confirmed that thyroid hormone directly stimulates the promoter region of the human renin gene through thyroid hormone response element-dependent mechanisms (36).…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that androgens modulate RAAS activity, thereby affecting blood pressure in a sex-specific manner and contributing to the hypertension observed in sGCα 1 -/-S6 mice (65). For example, renin 2 was reported to be an androgen-responsive gene (66,67). Moreover, overexpression of murine renin 2 in rats resulted in testosteronedependent hypertension (68).…”
Section: Figurementioning
confidence: 99%